5 - Machine à voter et résistance politique à l’élection présidentielle de 2018 en RDC - Atipo, Antomella Kornégie (Africa Development, 2022)
This article, which deals with the impact of the voting machine (VM) in the 2018 presidential election in the Democratic Republic of Congo, is based on the analysis and cross-referencing of documents from the Independent National Electoral Commission (CENI), the National Episcopal Conference of Congo (CENCO), local and international newspapers collected on the internet and other works on elections in Africa and the world and on electronic voting. It shows that CENI’s choice to use electronic voting to reduce fraud and improve the Congolese electoral process leads to resistance from some political parties and civil society organisations hostile to its use, who see it as a manoeuvre of the outgoing president to get his successor elected.